Associations of ore minerals in the deposits of the Seinäjoki district and the discussion on the ore formation - Yu.S. Borodaev; N.S. Bortnikov; N.N. Mozgova; N.A. Ozerova; P. Oivanen; V. Yletyinen (Bulletin of the Geological Society of Finland, 1983)
The mineral associations of the antimony deposits in the Seinäjoki region (Finland) are described on the basis of microprobe investigations. There are two ore associations: quartz-antimony and pyrrhotite- antimony. The latter is characterized by the presence of the new minerals seinäjokite and pääkkönenite first discovered in these deposits. The data obtained suggest that minerals were formed in the deposits under specific conditions: at relatively high temperatures for antimony deposition, and at extremely low sulphur fugacity for the hydrothermal process.